STRATEGIES OF DEFICIT WATER MANAGEMENT IN IRRIGATION OF SOYBEAN CROP - Gava, R.; Frizzone, J. A.; Snyder, R. L.; de Almeida, B. M.; de Freitas, P. S. L.; Rezende, R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
he use of water deficit controlled in irrigation reduces production costs.This study aimed to study the deficit irrigation at different stages of soybean. The experiment was conducted in the Biosystems Engineering Department -ESALQ/USP in Piracicaba-SP, soybean season 2012/13, in agreenhouse equipped with 48 drainage lysimeters 1.1m wide by 1.3m long and 0.75m deep was used. The experiment was made in randomized block design with four replications. For the application of treatments the crop cycle was divided into the following phenological period: S1(All of Vegetative Stage), S2(Beginning Bloom until Full Pod); S3(Beginning Seed until Full Seed)andS4(Beginning Maturity until Full Maturity). Crop evapotranspiration (ETc) was calculated by the Penman-FAO Montheith. For comparison with the full irrigation treatment (control), it was used Dunnett statistic test. The treatments consisted of four irrigation depths (30, 50, 100 and 150% of ETc) applied in each of the four subperiods, totalizing 12 treatments. The results showed that the water depths of deficit reduced yield when applied in full cycle. However, when applied only in subperiods showed no differences compared to full irrigation.